Effect of roasting parameters on soy‐butter product quality. (21st February 2013) - Agrahar Murugkar, Dipika; Kotwaliwale, Nachiket; Kumar, Manoj; Gupta, Chetan
Summary Effect of roasting temperature and time on the hardness, moisture content and colour of whole‐kernel of soybean was studied using response surface method (RSM). Colour of reference soy‐butter (RSB) was used to indicate the time and temperature suitable for roasting soybean kernels to prepare soy‐butter (SB). Temperature (160 °C) and time (90 min) for roasting were identified, soybean kernels were roasted, subsequently made into SB and compared with RSB on the basis of nutrient content, particle size, colour and rheology. SB contained 45 g% protein and 34 g% fat on dry matter basis. There was a significant difference (P < 0.05) between RSB and SB on the basis of L* values, D3, 2 and D4, 3. Rheology showed that SB samples behaved like a viscoelastic material. The mean apparent viscosity was significantly different (P < 0.0001) between SB (7.18 Pa.s) and RSB (4.72 Pa.s) which may be due to the significant difference in the particle size distribution (PSD). The Herschel‐Bulkley model could successfully explain the rheological behaviour of SB.